Non-null k-slant helices and their spherical indicatrices in Minkowski 3-space - Ergüt, Mahmut; Öztekin, Handan Balgetir; Aykurt, Sezin (My University, 2010)
In this study, we define non-null k-slant helices in Minkowski 3-space and give some characterizations for the non-null k-slant helix. © 2010 Institute of Advanced Scientific Research.
Keywords: K-slant helices; Minkowski space; Non-null curve